2016
DOI: 10.3920/bm2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a causal link between gut microbes, body weight gain and glucose metabolism in humans – towards treatment with probiotics

Abstract: Changes in the gut microbiota are associated with metabolic disorders, such as overweight and elevated blood glucose. Mouse studies have shown that gut microbiota can regulate metabolism with a mechanism related to gut barrier function. An impaired gut barrier permits the translocation of bacteria and their components which, when in contact with the sub-mucosal immune system, evoke metabolic inflammation and distract signalling in metabolically active tissues. Despite thorough research of the topic in animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 87 publications
1
47
1
1
Order By: Relevance
“…Dietary interventions for reducing obesity have been suggested that focus on calorie restriction, energy reduction, or a diet rich in prebiotic fibers, all of which are associated with an increased level of A. muciniphila in the host (Verhoog et al, 2019). For example, clinical trials have shown a significant increase in A. muciniphila in a calorie restriction study of 49 overweight and obese adults (Stenman et al, 2016). Diets rich in prebiotic fiber increased the number of A. muciniphila in the microbiome (Gomez-Gallego et al, 2016).…”
Section: Nutritional and Medicinal Approches For Modulation Of Akkermmentioning
confidence: 99%
“…Dietary interventions for reducing obesity have been suggested that focus on calorie restriction, energy reduction, or a diet rich in prebiotic fibers, all of which are associated with an increased level of A. muciniphila in the host (Verhoog et al, 2019). For example, clinical trials have shown a significant increase in A. muciniphila in a calorie restriction study of 49 overweight and obese adults (Stenman et al, 2016). Diets rich in prebiotic fiber increased the number of A. muciniphila in the microbiome (Gomez-Gallego et al, 2016).…”
Section: Nutritional and Medicinal Approches For Modulation Of Akkermmentioning
confidence: 99%
“…Since the discovery of a link between gut microbiota and obesity in 2006 (Turnbaugh et al, 2006, Ley et al, 2006), increasing evidence has been presented to suggest a causal relationship between gut microbiota and metabolic disorders (Stenman et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…Further, chronic treatment with dietary phenols from grapes, or cranberry extract, improved glucose tolerance and insulin sensitivity which was hypothesized to be due to A. muciniphila abundance (Anhe et al 2015, Roopchand et al 2015. Although A. muciniphila remains to be tested in humans, this is one example in an ever-expanding list of potential probiotics that could help lower glucose levels in type 2 diabetes (Le Barz et al 2015, Stenman et al 2015a. It is interesting to note that metformin treatment has been shown to alter the gut microbiota, with chronic treatment resulting in A. muciniphila abundance, as well as changes in bile acid levels, suggesting a gut microbiota-mediated role for metformin treatment (Lien et al 2014, Napolitano et al 2014, Shin et al 2014.…”
Section: Gut Microbiotamentioning
confidence: 99%